UPAYA MENINGKATKAN HASIL BELAJAR PESERTA DIDIK MELALUI METODE DISKUSI DALAM PEMBELAJARAN IPS DI KELAS VIIA SMPN 4 TAPUNG HILIR TAHUN PELAJARAN 2019/2020 - Yami yami (Journal of Education and Teaching, 2021)
Based on the formulation of the problem, the objectives to be achieved in this study are as follows. To find out the improvement of learning outcomes after using the discussion method, in learning Social Sciences the main discussion of the location and area of Indonesia in SMPN 4 Tapung Hilir The research design set in this study is classroom action research. There are four stages in action research, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. Based on the results of research conducted on students of Class VIIA IPS, amounting to 20 students, the researcher can collect data on student learning outcomes through written tests. The following are the results of pre-test and post-test learning of students taught using the discussion method. the level of mastery of students' material in the pretest as follows. value 40-46 with a frequency of 4 (20%), a value of 47 -53 with a frequency of 5 (25%), a value of 54-60 with a frequency of 4 (20%), a value of 61-67 with a frequency of 2 (10%), a value of 68-75 with a frequency of 5 (41.67%). Based on the data obtained in the pretest shows that the number of students who completed as many as 5 students or (25%), not complete as many as 15 students or (75%), while the first cycle of students who completed as many as 15 students or (75%), and incomplete 5 students or (25%).